Clinical Experience in a Large Cohort of Patients with Vitreoretinal Lymphoma in a Single Center. (3rd April 2021) - Giuffrè, Chiara; Cicinelli, Maria Vittoria; Marchese, Alessandro; Modorati, Giulio M.; Brambati, Maria; Ferreri, Andrés J. M.; Calimeri, Teresa; Ponzoni, Maurilio; Bandello, Francesco; Miserocchi, Elisabetta
ABSTRACT: Background/aims : To report our five-year experience on vitreoretinal lymphoma (VRL) as a single-center tertiary hospital. Methods : The ophthalmic, cytopathology, and onco-hematologic records of patients with VRL consecutively seen from 2014 to 2019 were reviewed. Results : Fifty-nine eyes of 31 patients with large B-cell VRL were included. Eighty-one percent has developed central nervous system lymphoma at the end of follow-up. Several different imaging findings were noted, including vitritis, leopard spot appearance, Bruch's membrane/RPE infiltrations, and ellipsoid zone disruption. A variable combination of MYD88-L265P mutation in the aqueous and/or in the vitreous and positive cytology/histology allowed to reach a definite diagnosis in all the patients. Therapies included intravitreal injections of methotrexate and rituximab, systemic chemotherapy, pan-encephalic radiotherapy, and hematopoietic stem cell transplantation. Conclusion : No definite guidelines exist for VRL management. It is crucial to collect as much data as possible from tertiary referral hospitals, which suitably manage a conspicuous number of VRL patients.